The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/md17100572
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycin V Suppresses Human Non-Small-Cell Lung Carcinoma A549 Cells by Inducing G2/M Phase Arrest and Apoptosis via the p53-Dependent Pathway

Abstract: Actinomycin V, extracted and separated from marine-derived actinomycete Streptomyces sp., as the superior potential replacement of actinomycin D (which showed defect for its hepatotoxicity) has revealed an ideal effect in the suppression of migration and invasion in human breast cancer cells as referred to in our previous study. In this study, the involvement of p53 in the cell cycle arrest and pro-apoptotic action of actinomycin V was investigated in human non-small-cell lung carcinoma A549 cells. Results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Similar discrepancies in cell lines have been reported in several previous studies. There might exist one target signaling pathway involved in both NSCLC cell lines that was not discussed in our study, 34 pathways 35 or the innate difference between cell lines 35,36 might also account for the discrepancy, and further exploration is needed.…”
Section: Discussionmentioning
confidence: 87%
“…Similar discrepancies in cell lines have been reported in several previous studies. There might exist one target signaling pathway involved in both NSCLC cell lines that was not discussed in our study, 34 pathways 35 or the innate difference between cell lines 35,36 might also account for the discrepancy, and further exploration is needed.…”
Section: Discussionmentioning
confidence: 87%
“…The cells were treated with serial concentrations of Act V and Act D (0–0.02 μM) for 48 h, and the IC 50 s were determined (Act D, which has been used for a long time in clinic, serves as a positive control here), as shown in Table 1 and our previous study [ 10 , 11 ]. Act V exhibited considerably stronger efficacy against cancer cells with a ten-fold lower IC 50 value compared to Act D. Act V and Act D induced cytotoxicity in human normal liver LO-2 and human embryonic kidney 293T cell lines in a concentration-dependent manner ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ], has a similar structure to that of Act D ( Figure 1 ). In our previous studies [ 10 , 11 ], Act V was found to be more cytotoxic to tumor cells than Act D. Moreover, Act V inhibited the migration and metastasis of breast cancer cells. In this aspect, Act V may be a potential substitute for Act D, so understanding the toxicological mechanisms of Act V and Act D is of great worth.…”
Section: Introductionmentioning
confidence: 93%
“…45 TP53 functions as a transcription activator of other targets downstream, including p21 and Bax, signifying that p53 can activate different pathways, including apoptosis. 4547 Previous studies have demonstrated CP 's ability to impede various types of human cancer cell growth via alteration of key apoptotic signaling pathways. 20,48…”
Section: Discussionmentioning
confidence: 99%